Elective End-to-side Portacaval Shunt: Results in 64 Cases. Issue 5785 (20th November 1971) - Hourigan, K.; Sherlock, Sheila; George, Phyllis; Mindel, S.
Abstract : In a series of 64 cases of elective end-to-side portacaval shunts performed for liver disease the success rate—in that the patient survived with a patent shunt, free of subsequent haemorrhage and severe encephalopathy—was 48%. The early postoperative death rate was 12·5% and the five-year survival 65%. Bleeding from oesophagogastric varices after blockage of the shunt was responsible for at least half of the early postoperative deaths, and most late deaths were due to liver failure. A decreased chance of late survival was associated with age over 40 years, active chronic hepatitis, and with a preoperative history of hepatocellular jaundice. Shunt blockage occurred in 16% of patients, and all bled again from oesophagogastric varices. Shunt block is more likely if the portal vein is calcified or thrombosed, and may be more likely if the portal vein diameter, as shown by splenic venography, is 1·5 cm or less. In survivors with a patent shunt the most serious late complication was chronic, severe portal-systemic encephalopathy, which occurred in 38%. Severe encephalopathy was associated with age over 40 years, a preoperative history of any degree of encephalopathy, diabetes mellitus, and with continued drinking in the alcoholic. Most patients who had portal-systemic encephalopathy in the first year postoperatively developed chronic disabling encephalopathy. A preoperative history of transient mild or moderate ascites did not seem adversely to influence the outcome.